Utilization of the Impella for hemodynamic support during percutaneous intervention and cardiogenic shock: an insight. (3rd October 2017) - Nalluri, Nikhil; Patel, Nileshkumar; Saouma, Samer; Anugu, Viswajit Reddy; Anugula, Dixitha; Asti, Deepak; Mehta, Varshil; Kumar, Varun; Atti, Varunsiri; Edla, Sushruth; Grewal, Rasleen K.; Khan, Hafiz M.; et al.
ABSTRACT: Introduction: Impella is a catheter-based micro-axial flow pump placed across the aortic valve, and it is currently the only percutaneous left ventricular assist device approved for high-risk percutaneous coronary intervention and cardiogenic shock. Areas Covered: Even though several studies have repeatedly demonstrated the excellent hemodynamic profile of Impella in high-risk settings, it remains underutilized. Here we aim to provide an up-to-date summary of the available literature on Impellas use in High risk settings as well as the practical aspects of its usage. Expert Commentary: Percutaneous coronary interventions in high rsk settings have always been challenging for a physician. Impella 2.5 and CP, have been proven safe, cost effective and feasible in High Risk Percutaneous coronary Interventions with an excellent hemodynamic profile.